Examining the Handling of Rohingya Refugees in Indonesia through the Lens of International Law and Maqāsid al-Shari’ah: An Exploration of Islamic Humanitarianism - Maula, Bani Syarif (Mazahib, 2024)
The issue of Rohingya refugees has gained significant attention globally and within Indonesian society, especially as many seek refuge in Aceh to escape persecution in Myanmar. The 1951 Vienna Convention and the 1967 Refugee Protocol form the global legal framework for refugee protection. However, Indonesia has not formally endorsed these statutes, so it is not legally bound to fulfill refugees’ basic needs. Despite this, Indonesia is obligated by the principle of non-refoulement, a customary international law or jus cogens, to manage Rohingya refugees entering its territory. This study examines Indonesia’s approach to refugee management through international law and maqāṣid al-sharī’ah, representing Islamic humanitarianism. Islamic scholarly discourse, specifically Fiqh al-Siyar, linked with maqāṣid al-sharī’ah, provides a foundation for contemporary humanitarian efforts. The study concludes that, under international law, Indonesia must protect refugees as part of implementing jus cogens. Additionally, from the maqāṣid al-sharī’ah perspective, Indonesia’s decision to welcome Rohingya refugees, despite not ratifying the 1951 Convention and the 1967 Protocol, exemplifies Islamic humanitarianism and acknowledges refugees’ inherent human rights.